Aetiology of sexually transmitted infections and response to syndromic treatment in southwest Uganda. Issue 6 (2nd December 2005) - Pickering, J M; Whitworth, J A G; Hughes, P; Kasse, M; Morgan, D; Mayanja, B; Van der Paal, L; Mayaud, P
Abstract : Objective: To determine the aetiology of genital ulcers and discharges in rural south western Uganda and to assess response to syndromic treatment. Method: A longitudinal, prospective study using laboratory testing and questionnaires to evaluate 561 adult men and women presenting with clinically verified genital ulcers, urethral, or vaginal discharge at a general outpatient clinic and two health centres between December 1999 and July 2001. Results: One third of patients had genital ulcers and two thirds discharges. There was good response to treatment in 461/508 patients (90.7%). Herpes simplex virus type 2 was found in 95/217 (43.8%) genital ulcers. In 24.1% of ulcer cases there was also a genital discharge. HIV seropositivity was high in ulcer cases (63.2%), with significantly more HSV2 and secondary bacterial infection than in seronegative cases. Neisseria gonorrhoeae was found in 135/204 (66.2%) male genital discharges. Female genital discharges were mostly associated with bacterial vaginosis (36.1%), Trichomonas vaginalis (18.9%), and candidiasis (18.6%). Conclusions: The aetiological pattern of STI syndromes reported will help inform revision of national STI guidelines. The importance of herpes simplex virus type 2, the variation in causes of genital ulcers according to HIV serostatus, the high frequency of multiple infections and secondary bacterial contamination of genital ulcers are notable. These results help explain the lack of effect of an STI intervention on HIV incidence in a recent trial in this area.